(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Introduction: ToRCH is an acronym for four congenital infections that are sometimes difficult to distinguish: Toxoplasmosis, Rubella, Cytomegalovirus (CMV), and Herpes Simplex Virus (HSV). This group of organisms produces serious Central Nervous System (CNS) and other infections, which are potentially preventable and treatable. Methods: Neonates and infants with hydrocephalus (N = 65) identified via the outpatient department of the National Institute of Neurosciences and Hospital (NINS&H), were prospectively screened for ToRCH antibodies. Hydrocephalus secondary to Tumor or Trauma was excluded from this study. Results: Evidence of 75.38 % (p = <0.05) patient was positive for TORCH antibodies. Toxoplasma Gondi (T. Gondii) IgG 18.5 % ( p= <0.05 ), CMV IgM 9.2 % (p = <0.05), CMV Ig G47.7% ( p = <0.5), Rubella, and HSV 1 & 2 antibodies were also identified. Conclusion: The vast majority of cases of neonatal hydrocephalus at one institution was post-infectious in etiology and related to ToRCH infections. Many of these cases could be prevented with improved screening and treatment. While study of a single institution may not be the representative of the entire population, further study and implementation of a standardized screening protocol would likely benefit this population. Bang. J Neurosurgery 2020; 9(2): 121-125